Personaliti Dan Kepimpinan Ulul Amri Guru Pendidikan Islam - Mardzelah binti Makhsin; Noriana Binti Abdullah (International Consortium of Education and Culture Research Studies, 2019)
This article aims to review and identify the characteristics of Ulul Amri's personality and leadership among Islamic Education teachers. A total of 109 students from 4 secondary schools in Kota Bharu district were randomly selected as respondents for the study. This study was conducted through a quantitative approach. The data were collected through a questionnaire translated from The Big Five Inventory (BFI) by John (1990) and Ulul Amri's Leadership following the Qur'an. The degree of reliability of the BFI instrument ranges from 0.62 to 0.77 while the Ulul Amri Leadership instrument is between 0.61 and 0.71. Descriptive analysis of frequencies and mins used for distribution analysis. Inference statistics that pearson correlation analysis is used to analyze the relationship between teacher personality and Ulul Amri Leadership. The significant level used is 0.05. The findings show that the most dominant personality dimensions of teachers are Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticism. The results of the correlation test showed that there was no significant relationship between the personality of the Islamic Education Teacher and the leadership of the Ulul Amri teacher except the personality of the agreeableness. The findings show that Islamic Education teachers have positive personalities such as Openness, Agreeableness, Extraversion and Conscientiousness. Meanwhile, Neuroticism with a negative personality teacher of Islamic Education has recorded the lowest mean. This finding shows that Islamic Education teachers in Kota Bharu have a good and positive perception among students. This is also a reflection of the expectation and dependence of the students on the Islamic Education teacher is very high. As Al-Qabisi's theory emphasizes the four qualities of a quality teacher in educating morals, ie by example, qudwah, unity, demonstration and understanding. Teachers through a qudwah approach or exemplary example can become themselves as followers or model roles to students by means of interaction inside and outside the classroom.